Harmful norms: Can social convention theory explain the persistence of female genital cutting in Africa? - Heather Congdon Fors; Ann-Sofie Isaksson; Annika Lindskog (Research Institute of Industrial Economics (IFN), 2021)
This paper investigates the explanatory power of social convention theory for explaining the persistence of female genital cutting (FGC) in a broad sample of African countries. While influential in policy circles, the idea that FGC is best described as a bad equilibrium in a social coordination game has recently been challenged by quantitative evidence from selected countries. These studies have pointed towards the importance of private preferences. We use novel approaches to test whether FGC is social interdependent when decisions also depend on private preferences. We test implications of the simple fact that according to social convention theory mothers will sometimes cut their daughters even if they do not support the practice. The substantial regional variation in FGC practices warrants investigation in a broad sample. Empirical results drawing on Demographic and Health Survey data from 34 surveys performed between 1992-2018 in 11 African countries suggest that cutting behavior is indeed often socially interdependent, and hence that it can be understood as a social convention. Our findings indicate that even if social convention theory does not provide the full picture, it should not be dismissed. Accordingly, interventions that acknowledge the social interdependence of cutting behavior are likely to be more successful than interventions that do not.
Keywords: D71; D91; I15; O55; 330; Female genital cutting; social convention theory; norms; Africa